Fibrotic encapsulation of orthodontic appliance in palate - Jananni Muthu; Sivaramakrishnan Muthanandam; Gubernath Umapathy; Anitha Logaranjani Kannan (Wolters Kluwer Medknow Publications, 2017)
Iatrogenic trauma though not serious is very common in dental practice. Orthodontic treatment can inflict such injuries as they are prolonged over a long period of time. Ill-fabricated orthodontic appliances, such as wires and brackets, or the patients' habits such as application of constant pressure over the appliance can traumatize the adjacent oral soft tissues. In rare cases, these appliances can get embedded into the mucosa and gingival tissues. This case report describes one such case of iatrogenic trauma to the palatal mucosa due to entrapment of a tongue spike appliance and its surgical management.